Urethral bulking agents for the treatment of recurrent stress urinary incontinence: A systematic review and meta-analysis. (September 2022) - Braga, Andrea; Caccia, Giorgio; Papadia, Andrea; Treglia, Giorgio; Castronovo, Fabiana; Salvatore, Stefano; Torella, Marco; Ghezzi, Fabio; Serati, Maurizio
Highlights: There is a lack of robust evidence about the best option after failure of a mid-urethral sling. Urethral bulking agents seem to be an effective and safe option for the treatment of recurrent stress urinary incontinence. Abstract: Recurrent stress urinary incontinence (rSUI) represents a major challenge for most clinicians as there is little evidence in the literature on the best option after sling failure. The objective of this study is to summarise the findings on the use of urethral bulking agents (UBAs) in the management of rSUI after the failure of a mid-urethral sling (MUSs). We performed a systematic review and meta-analysis, according to PRISMA 2020 guidelines, and selected eleven publications for inclusion in the analysis. We found that the overall cure and improvement rate ranged from 64% to 85% in the included studies, with a pooled value of 75%, compared with pooled failure and re-operation rates of 32% (95% CI: 22%–43%) and 25% (95% CI: 17%–34%), respectively. The I 2 test indicated significant statistical heterogeneity among the studies in relation to all the outcome measures; however, no risk of publication bias was found. To explore this heterogeneity in more depth, we performed a sub-group analysis of the two most commonly used bulking agents (Bulkamid and Macroplastique). The pooled values of the cure and improvement rate were 84% (95% CI: 77.0%–90.0%) and 80% (95% CI: 74.0%–85.0%) for Macroplastique and Bulkamid, respectively. We did not find significant heterogeneity or significant differences in the outcome measures in either group. For the first time in literature, our study provides an insight into the use of UBAs after failed MUSs. Although the results seem very promising, future studies with shared protocols are needed in order to recommend the use of UBAs in the treatment of recurrent cases.